Tough and adhesive nanostructured calcium phosphate thin films deposited by the pulsed plasma deposition method. Issue 96 (17th October 2015) - Boi, Marco; Bianchi, Michele; Gambardella, Alessandro; Liscio, Fabiola; Kaciulis, Saulius; Visani, Andrea; Barbalinardo, Marianna; Valle, Francesco; Iafisco, Michele; Lungaro, Lisa; Milita, Silvia; Cavallini, Massimiliano; et al.
<x xml:space="preserve">Abstract</x> Calcium phosphate thin films were deposited at room temperature by the pulsed plasma deposition method. After annealing at 600 °C, film mechanical properties and adhesion to the titanium substrate strongly improved.